The dollar during the Global Recession: US monetary policy and the exorbitant duty - Vania Stavrakeva; Jenny Tang (Federal Reserve Bank of Boston, 2018)
We document that during the Global Recession, US monetary policy easings triggered the "exorbitant duty" of the United States, the issuer of the world's dominant currency, by causing a dollar appreciation and a transfer of wealth from the United States to the rest of the world. This dollar appreciation runs counter to the predictions of standard macroeconomic models and works through two channels: (i) a flight-to-safety effect which lowered the expected excess returns of holding safe US government debt relative to foreign debt and (ii) lowered expected future inflation in the United States relative to other countries. We show that the signaling channel of monetary policy, whereby US policy easings are perceived to signal weaker future growth, can reconcile the novel empirical findings that we document.
Keywords: E52; F31; G01; 330; exchange rates; currency risk; risk premia; monetary policy; forward guidance; Federal Reserve information; interest rates; Global Financial Crisis